Focus Marking in Kuria - Landman, Meredith; Ranero, Rodrigo (My University, 2018)
This paper examines focus marking in Kuria. We propose an account of the syntax/semantics of the prefix /ne-/. This prefix displays a varied syntactic distribution, posing a puzzle as to what semantically unifies all of its uses. In focus constructions, /ne-/ obligatorily appears on a fronted (i.e. focused) phrase, whereas in simple declaratives, /ne-/ obligatorily appears pre-verbally. Following previous analyses of similar markers in Bantu (Schwarz 2007 for Kikuyu and Abels & Muriungi 2008 for Kiitharaka), we analyze /ne-/ uniformly as a focus marker that arises in a focus phrase in the left periphery. We support this account of /ne/ by presenting novel data that suggest that even when /ne-/ occurs pre-verbally, it still marks focus (VP focus or sentential focus.) We also show how /ne-/ differs syntactically from similar markers in other languages. For example, Kuria allows for the focus marker to appear internal to the focused constituent, in contrast with data from Kiitharaka (Abels & Muriungi 2008) and other languages (see Hartmann & Zimmermann 2009 for Guruntum). This paper thus discusses a range of data patterns relating to the Kuria prefix /ne-/, offering insight into a syntax/semantic puzzle as well as cross-linguistic variation in the realization of focus.
Keywords: Focus Marking; Kuria; Semantics